Antecedents of absenteeism among employees at SAMB: a case study / Norsuhada Baharudin - Baharudin, Norsuhada (2010)
Absenteeism constitute one of the problems that occurs in organization which affect not only the employee’s performance, but also the performance of the organization itself in term of productivity, production as well as services. The main objective of this research is to determine the factors that affect absenteeism at Syarikat Air Melaka Berhad. Besides, researcher also identifies the relationship between the factors towards absenteeism. The factors are individual lifestyle, workplace environment, general stress, and domestic problem. Researcher used questionnaire as a main instrumental in data collection method. Next, data that have been collected, will be analysed through frequency distribution, Pearson correlation and regression analysis. In general, the results of this research show that individual lifestyles the most influence towards absenteeism. This followed by the domestic problem, workplace environment and general stress.